Adipocyte factors, high-sensitive C-reactive protein levels and lipoxidative stress products in overweight postmenopausal women with normal and impaired OGTT. - Kassi, E; Dalamaga, M; Hroussalas, G; Kazanis, K; Merantzi, G; Zachari, A; Giamarellos-Bourboulis, E J; Dionyssiou-Asteriou, A (Maturitas, 2010)
OBJECTIVE: In obese postmenopausal women we assessed leptin and adiponectin, high-sensitive C-reactive protein (hsCRP), serum lipids and lipoxidative stress products: oxidized LDL (oxLDL) and malondialdehyde (MDA), in relation to impaired glucose tolerance (IGT). METHODS: Thirty-eight overweight/obese postmenopausal women were included in the study. Eighteen with normal glucose metabolism (NGT) and twenty with IGT, as it is diagnosed by OGTT. Serum leptin, adiponectin, hsCRP and MDA were measured at time 0 and 120 min of OGTT while total-cholesterol, LDL, HDL, triglycerides, oxLDL and anti-oxLDL autoantibodies at time 0. Insulin resistance (HOMA)/sensitivity (QUICKI) indexes were estimated. RESULTS: In subjects with NGT, hsCRP was positively correlated with fasting leptin and HOMA, while in subjects with IGT negatively with QUICKI. In both groups, hsCRP was positively correlated with fasting insulin, body mass index and waist circumference. Fasting adiponectin was positively associated with HDL in both groups and negatively with triglycerides in subjects with NGT as well as with serum glucose levels at time 120 min of OGTT in subjects with IGT. No association was observed between oxLDL and adipokines. A significant positive association was found between oxLDL and HOMA in subjects with IGT. During OGTT there was a significant increase of leptin and MDA levels in both groups. CONCLUSIONS: A relationship exists between obesity, insulin and sub-clinical inflammation. Leptin and lipid peroxidation are linked to hyperglycaemic state while oxLDL might be considered as a predictor of insulin resistance. Adiponectin could exert its antiatherogenic effect through HDL independently of the presence of IGT.
Keywords: Adipocytes; Adipokines; Adiponectin; Aged; Blood Glucose; Body Mass Index; C-Reactive Protein; Fasting; Female; Glucose Metabolism Disorders; Glucose Tolerance Test; Humans; Insulin; Leptin; Lipid Peroxidation; Lipids; Malondialdehyde; Middle Aged; Obesity; POSTMENOPAUSE; Reference Values; Waist Circumference